PO93 | Use of DOACS in heart transplantation recipients (Bleeding, Thrombosis and Vascular Biology)
Backgrounds and Aims: Direct Oral Anticoagulants (DOACs) are the treatment of choice for anticoagulation in patients with atrial fibrillation and venous thromboembolism. They have a superior efficacy and safety profile compared to Vitamin K Antagonists (VKAs), with less impact on the quality of life for patients as they do not require strict laboratory monitoring. We treated 3 heart transplant patients with DOACs: 1 male aged 69 and 2 females aged 67 and 64, respectively.